2023
DOI: 10.1002/ccr3.7611
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib associated temporal bone osteonecrosis

Abstract: Key Clinical Message Tyrosine kinase inhibitors have substantially improved survival in patients with gastrointestinal stromal tumors (GIST) and chronic myeloid leukemia (CML). We report the first association between long‐term imatinib use and temporal bone osteonecrosis, highlighting the importance of prompt ENT evaluation of such patients with new otological symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…McKenna et al [24] reported the case of a 75-year-old man who experienced bilateral ear pain and discharge for four months; he was treated with imatinib for a gastrointestinal stromal tumor. Subsequent examinations uncovered bilateral bony erosion and necrosis at the base of both external auditory canals.…”
Section: Imatinibmentioning
confidence: 99%
“…McKenna et al [24] reported the case of a 75-year-old man who experienced bilateral ear pain and discharge for four months; he was treated with imatinib for a gastrointestinal stromal tumor. Subsequent examinations uncovered bilateral bony erosion and necrosis at the base of both external auditory canals.…”
Section: Imatinibmentioning
confidence: 99%